2013
DOI: 10.1016/j.bbadis.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase-1 inhibition protects primary rat hepatocytes against bile salt-induced apoptosis

Abstract: Sphingosine kinases (SphKs) and their product sphingosine-1-phosphate (S1P) have been reported to regulate apoptosis and survival of liver cells. Cholestatic liver diseases are characterized by cytotoxic levels of bile salts inducing liver injury. It is unknown whether SphKs and/or S1P play a role in this pathogenic process. Here, we investigated the putative involvement of SphK1 and S1P in bile salt-induced cell death in hepatocytes. Primary rat hepatocytes were exposed to glycochenodeoxycholic acid (GCDCA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…S1P is the natural ligand of the GPCRs, S1PR1‐5, which are differentially expressed in different tissues . Previously, we had shown that S1PR2 is highly expressed in the liver and that TCA activates ERK1/2 and Akt through S1PR2 in rat primary hepatocytes .…”
Section: Resultsmentioning
confidence: 99%
“…S1P is the natural ligand of the GPCRs, S1PR1‐5, which are differentially expressed in different tissues . Previously, we had shown that S1PR2 is highly expressed in the liver and that TCA activates ERK1/2 and Akt through S1PR2 in rat primary hepatocytes .…”
Section: Resultsmentioning
confidence: 99%
“…Adapted from [111]. S1PR, S1PR1 (formerly named as EDG1) in 1998 [163], a total of five GPCRs have been identified as S1P-specific receptors (S1PR1-5) [152,[164][165][166]. S1PRs are differentially expressed in different tissues and the expression levels vary under different physiological and pathological conditions [167].…”
Section: Sphingosine 1-phosphate Signalingmentioning
confidence: 99%
“…In addition, spinster homologue 2 (Spns2), a member of the major facilitator superfamily, has been shown to mediate S1P secretion 30 , 31 . Extracellular S1P exerts its function via activating five different G protein coupled receptors (S1PR1–5) on the cell membrane to induce various cellular responses 32 , 33 , 34 ( Fig. 2 ).…”
Section: Sphingosine-1-phosphate and Sphingosine-1-phosphate Receptormentioning
confidence: 99%